Pancasila dalam Era Geopolitik 5.0: Tantangan dan Strategi Indonesia dalam Diplomasi Internasional - Sheva Yova Saahira; Tien Kamila Al Widad; Fieky Alfiyanti; Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya (Jurnal Hukum dan Sosial Politik, 2025)
The Geopolitics 5.0 era has introduced a new paradigm in which artificial intelligence (AI), digital technology, and global power dynamics are reshaping traditional diplomatic practices. As a nation rooted in the Pancasila ideology, Indonesia faces complex challenges in upholding its principles of humanity, unity, and social justice amid increasingly competitive geopolitical shifts. This research aims to analyze the relevance of Pancasila as a strategic framework for Indonesia’s diplomatic efforts in responding to the challenges of Geopolitics 5.0, while formulating policy recommendations aligned with national values. The study employs a qualitative approach, analyzing content related to Indonesia’s foreign policy, government documents, and recent diplomatic case studies. Supporting data is drawn from academic literature, archives of the Ministry of Foreign Affairs, and reports from global think tanks. The findings demonstrate that Pancasila serves as a critical foundation for shaping Indonesia’s adaptive diplomacy, particularly through: (1) soft power strategies rooted in cultural and creative economic assets, (2) digital diplomacy that prioritizes cyber sovereignty and freedom, and (3) leadership in multilateral forums. Pancasila’s values not only remain relevant but also provide Indonesia with a strategic advantage in building principle-driven diplomacy in the Geopolitics 5.0 era. Policy recommendations include strengthening digital human resource capacity, fostering collaborative technology research, and advancing public diplomacy initiatives.